The Daily Pattern of Expression of Leptin and Ghrelin O-Acyl Transferase Under Various Lighting Schedules in the Whole Brain of Zebrafish (Danio rerio) - Mondal, Gopinath; Khan, Zeeshan Ahmad; Devi, Sijagurumayum Dharmajyoti; Labala, Rajendra Kumar; Chattoraj, Asamanja (Frontiers in Ecology and Evolution, 2021)
The influence of Artificial Light at Night (ALAN) is a severe interference in the biological rhythm of organisms. Feeding dysregulation might be the main factor responsible for developing metabolic diseases. The molecular basis of these physiological dysregulations is yet to be elucidated. The effect of light on appetite-regulating signal in the brain of zebrafish is still unknown. Therefore, the present study aimed to find the daily mRNA expression profile of two significant appetite and energy balancing peptide hormone (leptin) and enzyme (goat) in the brain in various illumination LD (12Light:12Dark), LL (24L), DD (24D). Moreover, the Ga-SI, protein level of the two appetite-regulating peptides, brain and serum melatonin, are measured after 72 hours of incubation under three different photic conditions. The immunohistochemical localization of the primary mediators of appetite regulators, leptin and goat, in the brain of zebrafish, under different photic conditions is reporting first time in zebrafish. The study revealed that in continuous light after 72 hours of incubation, feeding (Ga-SI) is found the highest, and the translational level of two appetite-related genes (leptin and goat) are lowest compared to LD. In the continuous dark, this relation becomes opposite. The daily variation of mRNA expression of leptin and goat in LD shows peak expression at the light and dark phase, respectively. This pattern abolished in continuous conditions. Thus, our study suggests that the photoperiod (zeitgeber) may influence the expression pattern (daily variation) of appetite regulating peptide hormone and enzyme in the brain of zebrafish.